A CONTRASTIVE STUDY OF ENGLISH AND IZHIA NUMERALS (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
This paper investigates the syntactic relation between the Izhia numerals and that of the English language, and examines how the numerals in both languages can enter into relationship with the nouns to form a determiner phrase. The study uses the contrastive analysis and the minimalist program as effective tools for identifying, predicting and generalizing syntactic structural similarities and dissimilarities, which may pose difficulties in second language learning or ease second language learning. Ten senior secondary three (SS3) students, aged between fifteen and seventeen randomly selected from Izhia Boys Secondary School were used as population for this study. A three-part questionnaire was administered to the respondents on determiners in both languages in the area of numerals. Numerals in the two languages include; one, two for cardinal and first, second for ordinal numerals from the English perspective and naanu, ebo  for cardinal and ke mbu ke ebo for ordinal from the Izhia perspective. The findings reveal that numerals in both languages are grouped into cardinal and ordinal and are functionally similar but structurally dissimilar, as the English numerals occur only in pre-position in their determiner phrase  (DP) structures while in Izhia, the reverse is the case as the numerals appear in post-position in their DP system. The study also reveals that there is co-occurrence of determiners in Izhia DP with numerals which is not common in English. The study brought to the fore the fact that nouns can co-occur in DP with cardinal numerals in the two languages under study. On this premise, it is realized that the knowledge of the dissimilarities in the structures of the L1 and the L2 can enhance proficiency and good performance in the teaching and learning of English language as a second language. The study therefore recommends that there is need to design a teaching hypothesis or mechanism that will draw the attention of the L2 learners to the differences in the structure of both languages to enable them achieve international intelligibility.
Keywords: Contrastive,Study,English,Izhia,Numerals